Safety and Efficacy of Subcutaneous Rituximab in Previously Untreated Patients with CD20+ Diffuse Large B-Cell Lymphoma or Follicular Lymphoma: Results from an Italian Phase IIIb Study. (27th January 2022) - Petrini, Mario; Gaidano, Gianluca; Mengarelli, Andrea; Consoli, Ugo; Santoro, Armando; Liberati, Anna Maria; Ladetto, Marco; Fraticelli, Vincenzo; Guarini, Attilio; Mannina, Donato; Ferrando, Paola; Corradini, Paolo; et al.
Abstract : Subcutaneous (SC) rituximab may be beneficial in terms of convenience and tolerability, with potentially fewer and less severe administration-related reactions (ARRs) compared to the intravenous (IV) form. This report presents the results of a phase IIIb study conducted in Italy. The study included adult patients with CD20+ DLBCL or FL having received at least one full dose of IV RTX 375 mg/m 2 during induction or maintenance. Patients on induction received ≥4 cycles of RTX SC 1400 mg plus standard chemotherapy and FL patients on maintenance received ≥6 cycles of RTX SC. Overall, 159 patients (73 DLBCL, 86 FL) were enrolled: 103 (54 DLBCL, 49 FL) completed induction and 42 patients with FL completed 12 maintenance cycles. ARRs were reported in 10 patients (6.3%), 3 (4.2%) with DLBCL and 7 (8.1%) with FL, all of mild severity, and resolved without dose delay/discontinuation. Treatment-emergent adverse events (TEAEs) and serious adverse events occurred in 41 (25.9%) and 14 patients (8.9%), respectively. Two patients with DLBCL had fatal events: Klebsiella infection (related to rituximab) and septic shock (related to chemotherapy). Neutropenia (14 patients, 8.9%) was the most common treatment-related TEAE. Two patients with DLBCL (2.8%) and 6 with FL (7.0%) discontinued rituximab due to TEAEs. 65.2% and 69.7% of patients with DLBCL and 67.9% and 73.6% of patients with FL had complete response (CR) and CR unconfirmed, respectively. The median time to events (EFS, PFS, and OS) was not estimable due to the low rate of events. At a median follow-up of 29.5 and 47.8 months in patients with DLBCL and FL, respectively, EFS, PFS, and OS were 70.8%, 70.8%, and 80.6% in patients with DLBCL and 77.9%, 77.9%, and 95.3% in patients with FL, respectively. The switch from IV to SC rituximab in patients with DLBCL and FL was associated with low risk of ARRs and satisfactory response in both groups. This trial was registered with NCT01987505 .